The Role of Phlebotomy () and Wet Cupping () to Manage Dizziness and Vertigo From the Viewpoint of Persian Medicine - Gholamreza Kordafshari MD; Mohammad Reza Shams Ardakani PhD; Mansoor Keshavarz MD, PhD; Mohammad Mehdi Esfahani PhD; Esmaeil Nazem; Maryam Moghimi MD, PhD; Arman Zargaran PharmD, PhD; Hoorieh Mohammadi Kenari MD, PhD (SAGE Publishing, 2017)
Dizziness and vertigo are the most common complaints of patients that has a high economic burden on the health system. In modern medicine, treatment for dizziness and vertigo consists of chemical pharmacological therapy. Although these drugs are useful in controlling the disease, their side effects and inefficiency in full control of the disease require the use of complementary medicine in this field. Persian medicine consists of valuable experiences of Persian medicine scholars based on the theory of humors and temperaments. In Persian medicine, 2 types of disease are presented: dizziness ( sadar ) and vertigo ( dovar ). Persian medicine physicians expressed a different mechanism of action than modern medicine for these diseases. They believed that accumulation of abnormal humors, reeh (normal bloating) or causative pathologic substances, is the basic cause of sadar and dovar and that the most important treatment is cleansing the body, particularly the head from accumulated substances by bloodletting methods.